TINGKAH LAKU MAKAN LUTUNG JAWA Trachypithecus auratus DI KAWASAN PANCURAN 7 BATURADEN GUNUNG SLAMET JAWA TENGAH - Dwi Eliana; Erie Kolya Nasution; Indarmawan Indarmawan (Scripta Biologica, 2017)
Javan Langur (Trachypithecus auratus) has an important ecological role in conserving the forest as their habitat by spreading seeds of fruits of their food. They are also responsible for the pattern of the plant diversity and forest regeneration as their habitat. Unfortunately, Javan Langur has been listed on Appendix II of CITES and categorized as vulnerable by the IUCN. Pancuran 7 Baturaden on the Mount Slamet slope is one of the few Javan Langur habitats in Java. Information on the Javan Langur in this area was inadequate. Therefore this study was aimed to get information on the type of food and the feeding behavior of Javan Langur, particularly in Pancuran 7 Baturaden. This study used a survey method, and the Animal Scan sampling technique was applied. The variables observed were sex ratio, population size, eating position, eating process, feeding locations, feeding duration, including the food type of the Javan Langur. Observed data for each variable were analyzed descriptively as percentages, and the results showed the Javan Langur were eating by sitting and standing, were marking trees to feed, were using hands and mouth to eat, were eating leaves and fruit, were eating on the trees and bushes. There were nine plant species as their food variety, while Matoa fruit and leave (Pometia  pinnata) were their preferred foods.